Черный, Белый и Рыжий: по мотивам книг Сесила Алдина / А. А. Усачев ; [рис. С. Алдина] - Усачев Андрей Алексеевич (Мелик-Пашаев, 2012)
Для дошкольников. Экземпляры: ДБ (20120912) / Инвентарный номер: 41138zzzzz / Цена: 260.03 / Сис.шифр: 84(2) / Авт.знак: У 74 / ГРНТИ: 17.82.93 / ББК: 84(2=Рус)